The late Pleistocene horned crocodile Voay robustus (Grandidier & Vaillant, 1872) from Madagascar in the Museum für Naturkunde Berlin - C. Bickelmann; N. Klein (Fossil Record, 2009)
Crocodylian material from late Pleistocene localities around Antsirabe, Madagascar, stored in the collection of the Museum für Naturkunde, Berlin, was surveyed. Several skeletal elements, including skull bones, vertebrae, ribs, osteoderms, and limb bones from at least three large individuals could be unambiguously assigned to the genus Voay Brochu, 2007. Furthermore, the simultaneous occurrence of Voay robustus Grandidier & Vaillant, 1872 and Crocodylus niloticus Laurenti, 1768 in Madagascar is discussed. Voay robustus and Crocodylus niloticus are systematically separate but similar in stature and size, which would make them direct rivals for ecological resources. Our hypothesis on the extinction of the species Voay, which was endemic to Madagascar, suggests that C. niloticus invaded Madagascar only after V. robustus became extinct.doi:10.1002/mmng.200800007